2020
DOI: 10.1017/s0022215120002261
|View full text |Cite
|
Sign up to set email alerts
|

How I do it: a simulator of the ear for developing otomicroscopy skills during the coronavirus disease 2019 pandemic

Abstract: Objective To develop a simulator of the external auditory canal and tympanic membrane that enables surgical trainees to practise their otomicroscopy skills, which is particularly valuable at a time where there is limited patient contact because of the coronavirus disease 2019 lockdown. Methods A simulator of the external auditory canal and tympanic membrane was made using a cardboard bowl, a 2 ml syringe and a latex glove. The simulator was used to practise otomicroscopy skills, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…1, flowchart) and study characteristics are provided in Table 2. Twenty-one studies (18–38) described only development/technical aspects of simulation models and were categorized as “descriptive.” Twenty-five studies (5,39–62) evaluated models for training/educational purposes or assessment of MT skills and were categorized as “educational.” Overall, we found 31 unique physical models and three different VR models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, flowchart) and study characteristics are provided in Table 2. Twenty-one studies (18–38) described only development/technical aspects of simulation models and were categorized as “descriptive.” Twenty-five studies (5,39–62) evaluated models for training/educational purposes or assessment of MT skills and were categorized as “educational.” Overall, we found 31 unique physical models and three different VR models.…”
Section: Resultsmentioning
confidence: 99%
“…A majority of the survey studies and one observational study had a Kirkpatrick level 1 educational outcome such as perceived realism of the model and/or opinion on its potential use for training (5,44,46,48,56,57,61). Generally, the different models were perceived to be of moderate to high realism and potentially beneficial to trainees' skills acquisition.…”
Section: Outcomes Of Simulation-based Trainingmentioning
confidence: 99%
“…With these challenges faced by Otolaryngology residents, the need for simulation models has become more apparent for developing skills that include otomicroscopy, myringotomy and ventilation tube insertion. [11][12][13] A recent international survey of Otolaryngologists during the Covid-19 pandemic reported that 90 percent of respondents supported the use of surgical simulation in training. However, many did not have access to these tools at their institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Given the reduction in clinical ENT exposure during the Covid-19 pandemic, this simulation session was extremely valuable in improving my confidence in managing such emergencies. Recent literature also shows innovative techniques in simulating aural microscopy skills and myringotomy and grommet insertion using simple tools ( Shenton and Aucott, 2020 ), which are useful in gaining and maintaining existing skills. In this way, simulation can be valuable adjunct for training during this period.…”
Section: Tipmentioning
confidence: 99%